Impact of COVID-19 on airlines industry / Baderisang Mohamed and Maryam Nabila Muhammad - Mohamed, Baderisang; Muhammad, Maryam Nabila (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Corona virus (COVID-19) is an infectious disease which is caused by a newly discovered corona virus. People who are infected with this corona virus will have mild to moderate respiratory disease and will recover quickly, even without the need for special care. Essentially, the droplets of saliva or discharge from the nose of the infected person spread through coughs or sneezes that caused the corona virus to develop (World Health Organization, 2020). The corona virus pandemic (COVID-19) has disrupted business operations in various industries especially the airline industry. The disease is easily transmitted to people around the world. It has affected both, domestic and international travelling activities in the airline industry.